2005
DOI: 10.1159/000089672
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Thymidine Phosphorylase in Chronic Glomerulonephritis and Its Role in Tubulointerstitial Injury

Abstract: Chronic tubulointerstitial injury (CTI), commonly a sequel to chronic glomerulonephritis (CGN), is associated with the proliferation of new blood vessels. Angiogenesis is an essential process in chronic inflammation, and is controlled by a number of angiogenic factors including thymidine phosphorylase (TP). Knowledge of TP in renal disease is still rudimentary, and its role in CGN has not been explored. We analyzed the expression of TP by RTPCR, immunohistology and in situ hybridization in 20 human kidneys wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…Moreover, we also found that, similar to cancer cells, rhTP can promote the proliferation and invasion abilities of CAFs in vitro. A similar promoting role of TP on interstitial brosis in glomerulonephritis was also reported in a previous study (41). Bone resorption occurred more frequently in PDX mouse models in the TP + CAFs group than in the group without TP + CAFs.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we also found that, similar to cancer cells, rhTP can promote the proliferation and invasion abilities of CAFs in vitro. A similar promoting role of TP on interstitial brosis in glomerulonephritis was also reported in a previous study (41). Bone resorption occurred more frequently in PDX mouse models in the TP + CAFs group than in the group without TP + CAFs.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, VPA has been shown to demonstrate anti-cancer activity in breast cancer via induction of TP or thymidine phosphorylase expression ( Terranova-Barberio et al, 2016 ). The up-regulation of TP contributes to angiogenesis, which may also play a critical role in the progression of fibrosis ( Wang et al, 2006 ). Interestingly, in our qPCR array, we also observed significantly increased expression of TP in ECs following VPA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Furthermore, TP is upregulated in chronic glomerulonephritis (a renal disease characterized by inflammation of the glomeruli) where it probably plays a critical role in the progression of interstitial fibrosis. 42 Moreover, TP is expressed in atherosclerosis. Macrophages, foam cells, and giant cells from both aortic and coronary plaques were found to be immunoreactive for this angiogenic factor, suggesting that TP may play a role in the pathogenesis of atherosclerosis.…”
Section: B Tp In Inflammatory Diseasesmentioning
confidence: 99%
“…Reumatoid arthritis [44][45][46][47][48][49][50] Atherosclerosis 43 Psoriasis 38,39 Inflammatory bowel disease 40,41 Chronic glomerulonephritis 42 MNGIE [51][52][53][54][55][56][57][58] deficiency in skeletal muscle leading to mitochondrial disorders characterized by hypertrophic cardiomyopathy and encephalopathy. 61 Thus, more investigations are needed to clarify the exact role of TP deficiency in MNGIE development.…”
Section: Inflammatory Diseasesmentioning
confidence: 99%